Experimental Study on the Burning Characteristics of Photovoltaic Modules with Different Inclination Angles Under the Pool Fire - Jingwen Xiao; Dong Lin; Jia Zeng; Shuai Zhang; Jinlong Zhao (Fire)
Mountain photovoltaic (PV) power stations cover vast areas and contain dense equipment. Once direct current arc faults occur in PV modules, they can pose a serious thermal threat to surrounding facilities and combustible materials, potentially resulting in a PV array fire accident. In this work, a series of PV module fire experiments were conducted to investigate the burning characteristics of PV modules exposed to the pool fire. The burning process, burning damage extent, and temperature distribution were measured and analyzed. The results showed that the surfaces of PV modules exhibited different burning characteristics due to the pool fire. Based on different characteristics, the front side was classified into four zones: intact zone, delamination zone, carbonization zone and burn-through zone. The back side was similarly divided into four zones: undamaged backsheet zone, burnt TPT zone, cell detachment zone and burn-through zone. Meanwhile, the burning process and surface temperature rise rate of intact PV modules were significantly lower than those of cracked modules at the same inclination angle. Cracked modules exhibited a heightened susceptibility to being rapidly burnt through by the pool fire. As the inclination angle increased from 0° to 60°, the burning damage extent and the expansion rate of high-temperature regions initially ascended and subsequently decreased, reaching their maximum at the inclination angle of 15°. These findings can offer valuable insights that can serve as a reference for the fire protection design and risk assessment of mountain PV power stations, ensuring their safe operation.